THE EVOLUTION OF THE SEXUALLY SELECTED SWORD IN XIPHOPHORUS DOES NOT COMPROMISE AEROBIC LOCOMOTOR PERFORMANCE. (28th March 2014) - Oufiero, Christopher E.; Meredith, Robert W.; Jugo, Kristine N.; Tran, Paulina; Chappell, Mark A.; Springer, Mark S.; Reznick, David N.; Garland, Theodore
<x xml:space="preserve">Abstract</x> Sexual selection can increase morphological diversity within and among species. Little is known regarding how interspecific variation produced through sexual selection affects other functional systems. Here, we examine how morphological diversity resulting from sexual selection impacts aerobic locomotor performance. Using Xiphophorus (swordtail fish) and their close relatives (N = 19 species), we examined whether the evolution of a longer sexually selected sword affects critical swimming speed. We also examined the effect of other suborganismal, physiological, and morphological traits on critical swimming speed, as well as their relationship with sword length. In correlation analyses, we found no significant relationship between sword length and critical swimming speed. Unexpectedly, we found that critical swimming speed was higher in species with longer swords, after controlling for body size in multiple regression analyses. We also found several suborganismal and morphological predictors of critical swimming speed, as well as a significant negative relationship between sword length and heart and gill mass. Our results suggest that interspecific variation in sword length is not costly for this aspect of swimming performance, but further studies should examine potential costs for other types of locomotion and other components of Darwinian fitness (e.g., survivorship, life span).